Tradução de termos simples, expressões fixas e semifixas em ciência política e economia política: um estudo baseado em corpus - Serpa, Talita [UNESP] (2011)
This study discusses translations in English concerning the areas of Political Science and Political Economy, written by Fernando Henrique Cardoso & Enzo Falleto; and Antonio Carlos Bresser-Pereira. Our research project draws on CorpusBased Translation Studies (BAKER, 1993, 1995, 1996, 2000; CAMARGO, 2005, 2007), Corpus Linguistics (BERBER SARDINHA, 2004; TOGNINI-BONELLI, 2001) and on some concepts of Terminology (BARROS, 2004; KRIEGER & FINATTO, 2004). For compiling the comparable corpora in Portuguese and in English, we selected articles from Brazilian journals and from international journals of Political Science and Political Economy. We also present four samples of bilingual glossaries with the terms of these subareas in their cotexts.